THE RESPONSIBILITY OF PDAM TIRTA DHARMA IN DOMPU REGENCY TO THE CLEAN WATER CONSUMER - Akbar, M.Hijratul (Jurnal IUS, 2015)
Research method is conduct by empiric-juridic approach, research on legal regulation especially Law on Consumer Protection and Law on Raw Water Sources, and supported by interviews on informant and respondent. The research result shows that the Law on Consumer Protection has been regulated on bussinesman responsibility in accordance with Article 19 Law on Consumer Protection that bussinesman responsible to give a compensation for the damages, contamination, and/or consumer loss as the result of consuming goods or services that produces or traded. PDAM responsibility constrained by several factors like limited of raw water sources and limited public budgetting for clean water to manage by PDAM, and leak of pipeline because lack of maintenance by PDAM. Consumer dispute settlement on clean water, the society is not fully aware therefore socialization by government is needed, establishment of BPSK and the regulation in form of local government regulation that can protect unresponsible businessman activity. Â Keyword : Consumer Protection, Clean Water